2017
DOI: 10.4155/fsoa-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes from Lung Cancer and Diabetes Mellitus: A Matched Case–Control Study

Abstract: Aim:This case–control study examined the impact of diabetes mellitus (DM) on survival in lung cancer patients and lung cancer on glycemic control in DM.Materials & methods:Patients with a new lung cancer diagnosis and DM (n = 124) were matched to 124 lung cancer patients without DM. Laboratory results and DM and cancer therapies were obtained from electronic records.Results:Five-year overall survival for lung cancer patients with and without DM was 20 versus 29% (p = .12). Glycemic control among DM patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 23 publications
2
37
1
Order By: Relevance
“…On the contrary, several studies found that diabetes does not impact overall survival in lung cancer [94], and may even be associated with longer survival rates [85]. Furthermore, another study found that diabetes may play a protective role against lung metastasis [95], suggesting that the role of diabetes in lung cancer needs further clarification.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…On the contrary, several studies found that diabetes does not impact overall survival in lung cancer [94], and may even be associated with longer survival rates [85]. Furthermore, another study found that diabetes may play a protective role against lung metastasis [95], suggesting that the role of diabetes in lung cancer needs further clarification.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Case selection was similar to that described for previous studies [15][16][17][18]. Mayo Clinic Institutional Review Board approval was obtained for this retrospective, case-control study.…”
Section: Case Selectionmentioning
confidence: 99%
“…On the contrary, several studies found that diabetes does not impact overall survival in lung cancer [94], and may even be associated with longer survival rates [85]. Furthermore, another study found that diabetes may play a protective role against lung metastasis [95], suggesting that the role of diabetes in lung cancer needs further clarification.…”
Section: Clinical Presentationmentioning
confidence: 99%